A taxonomic note on Crossorhombus azureus (Alcock 1889) (Family: Bothidae, Order: Pleuronectiformes) from the south-west coast of India - J. Nair, Rekha; Gopalakrishnan, A. (Indian Journal of Fisheries, 2015)
Five species of the bothid genus Crossorhombus viz.,Crossorhombus azureus, C. valderostratus, C. kobensis, C. kanekonis and C. howensis are currently recognised worldwide. Of these, only two species, C. azureus, and C. valderostratus have been recorded in India. Descriptions of C. azureus are mostly based on the first published work of Alcock (1889) and further addition to the knowledge is scanty. Hence an attempt is made here to update the knowledge on the species. Detailed description of the species is presented in this paper based on morphometric and meristic measurements and biological observations on 57 specimens collected from Neendakara on the south-west coast of India. Sexual dimorphism is noticed with males having a series of azure spots on the head. Results of the t- test supports the external differences shown by males and females.